Dialectal variation of duration patterns in Finnmark North Sámi quantity - Hiovain, Katri; Šimko, Juraj; Vainio, Martti (The Journal of the Acoustical Society of America, 2020)
Ternary length contrast is a rare phonological feature, investigated here both in terms of its realization and possible undergoing changes. In North Sami, a phonetically under-documented and endangered Fenno-Ugric language spoken by indigenous people in Northern Europe, the ternary quantity contrast is assumed to be signalled by a progressive lengthening of a consonant and a compensatory shortening of the previous vowel. This study evaluates this assumption and compares the realization of the length contrasts in two dialects, the Western and Eastern Finnmark North Sami. The results show that while the contrast between the short and the two longer quantities is robustly signaled regardless of the dialect, the durational differences between the two longer quantities are maintained only in the Eastern dialect. On the other hand, a vowel quantity contrast independent of the quantity of the following consonant is present in the Western but not in the Eastern dialect. Further, comparing the phonetic realization of the ternary quantity contrast for speakers of different ages presents evidence of a language change: the results indicate an ongoing neutralization of the ternary contrast in younger speakers, which points to a possible disappearance of this rare typological feature in Finnmark North Sami. Peer reviewed